Kajian pemasaran komoditi ikan beku PT. Hui Mei Wei Aquatic Product Tranding di Pelabuhan Perikanan Samudera Kendari - Rahman, La Ode; La Ola, La Onu; Mansyur, Akhmad; Risfandi (Universitas Halu Oleo, 2024)
This study aims to examine the processing of frozen fish and frozen fish marketing system.The experiment was carried out at PT. Hui Mei Wei Aquatic Product Trading PPS Kendari in February-March 2022. The sampling technique was selected by purposive sampling and data collection techniques were carried out by interviews, observation, recording and literature studies consisting of primary data and secondary data. The data analysis used was the profit formula, namely π=TR-TC. The results of the study concluded that the processing of frozen fish by PT. Hui Mei Wei Aquatic Product Trading starts from fish weighing, cleaning, sorting, freezing, packaging and marketing. Marketing system of frozen fish in PT. Hui Mei Wei Aquatic Product Trading, namely starting with following the wishes of buyers in Hong Kong, and then preparing frozen fish commodities according to demand and seeking shipping services to deliver the goods to the destination country (Hong Kong).